How to Survive Without Commons? Conflicts Over Forests and Coping Strategies of the Poor in the Post-Feudal Period in the Northeastern Part of the Habsburg Empire - Popek, Joachim (International Journal of the Commons, 2025)
The article deals with the conflicts over common forests and peasants’ common rights in the first decades after the abolition of serfdom in the north-eastern part of the Austrian Empire (Galicia). The analysis focuses on the revolutionary agrarian reforms that had a direct impact on the existential condition of former serfs. On the one hand, the peasants received the land they had been cultivating and no longer had to work for free for the nobility. On the other hand, they lost access to the common lands and common rights that had been essential for their everyday life. As a result, the peasants developed their own coping strategy due to the lack of resources necessary for survival, i.e. through illegal acts such as thefts of natural resources in the manor forests.
Keywords: forests; common lands; common rights; peasants; coping strategy; Eastern Europe; Galicia